Fabrication of hydroxyapatite-based nano-gold and nano-silver-doped bioceramic bone grafts: Enhanced mechanostructure, cell viability, and nuclear abnormality properties - Demirel, M.; Aslan, N.; Aksakal, B.; Arslan, M. E. (Wiley, 2023)
In this study, nano-gold (nAu) and nano-silver (nAg) were doped at the molar ratios of Molar5-Molar30 to the Hydroxyapatite (HAp)-based bioceramic bone graft synthesized by the sol-gel method. The effects of nAu and nAg on structural, mechanical, cell viability, and nuclear abnormality of the synthesized bioceramic grafts were evaluated. The chemical and morphological properties of the bone grafts after production were examined through XRD and SEM-EDX analyses and mechanical tests. To determine the biocompatibility of the bone grafts, cell viability tests were performed using human fibroblast cells. In the cytotoxicity analyses, only HAp and HAp-nAu5 grafts did not show toxicological properties at any concentration, while HAp-nAg5 among the nAg-containing grafts gave the best results at the 200-100 mu g/mL concentrations and showed significant cytotoxicity in human fibroblast cells. The other nAu-containing grafts showed toxicological properties in the concentration range of 200-50 mu g/mL and nAg-containing grafts in the concentration range of 200-100 mu g/mL against the negative control. The micronucleus (MN) analyses showed that the lowest total MN and L (lobbed) amounts, while the lowest total N (notched) amount, was obtained from the only HAp graft. It was found that the nAg-doped bone grafts gave higher total MN, L, and N amounts compared to the nAu-doped bone grafts. Furthermore, while the mean nuclear abnormality (NA) values of all grafts gave close results, the highest values were again obtained from the nAg-doped bone grafts.
Keywords: bioceramic; biograft; cell viability; nano-gold; nano-silver; nuclear abnormality